Breviscapine reverses doxorubicin resistance in breast cancer and its related mechanisms - Weijiang Fu; Jie Song; Haiying Li (Thoracic Cancer, 2023)
Abstract Background Based on the effect of breviscapine (BRE) on reversing drug resistance of human breast cancer cell line MCF‐7/doxorubicin (Dox), the mechanism was preliminarily explored. Methods The methyl thiazolyl tetrazolium (MTT) method was introduced to detect inhibitory effect of Dox alone or in combination with BRE on MCF‐7 (M) and MCF‐7/Dox (MD) cells, and the inhibitory concentration (IC50) was obtained. Cell apoptosis and Dox concentration was assessed by flow cytometry. The drug resistance multiple and reversal fold were calculated. Western blot was performed to evaluate the expression of Bcl‐2, Bax, EGFR, p‐EGFR, P‐gp, caspase‐3, and cleaved‐caspase‐3 protein in cells. The efflux of Rho‐123 was measured by flow cytometry and fluorescence microscopy. Results The IC50 of Dox on MD and M cells was 16.67 and 0.71 μg/mL, respectively, with a drug resistance ratio of 23.48 times. The IC50 of Dox combined with BRE on MD cells was 5.62 μg/mL, with a reversal ratio of 2.97 times. BRE greatly enhanced Dox‐induced apoptosis of MD cells. Bax and cleaved‐caspase‐3 (proapoptotic protein) expression were obviously increased, while Bcl‐2 (antiapoptotic protein) expression was significantly decreased after BRE treatment. BRE inhibited EGFR activation and P‐gp expression. BRE increased the intracellular accumulation of Dox in MD cells by P‐gp. Conclusion BRE could increase the MD sensitivity to Dox via increasing Bax and cleaved‐caspase‐3 expression and inhibiting Bcl‐2 expression, thereby promoting cell apoptosis. BRE reversed Dox resistance of MD cells by increasing Dox intracellular accumulation through inhibiting P‐gp expression via EGFR.